Corrosion mechanisms of plasma welded Nickel aluminium bronze immersed in seawater - Dobson, Tamsin; Larrosa, Nicolas; Reid, Mark; Rajamudili, Kuladeep; Ganguly, Supriyo; Coules, Harry (Elsevier, 2024)
Nickel Aluminium Bronzes (NAB) are copper-based multi-phase alloys used extensively in marine applications. NAB is vulnerable to seawater corrosion, however the interaction between its corrosion mechanisms and real-world factors including biofouling, weld microstructure and residual stress are poorly understood. Seawater corrosion tests were performed on plasma-welded NAB in laboratory and marine environments, demonstrating that the retained β’ phase in the Heat Affected Zone (HAZ) experiences Selective Phase Corrosion (SPC), whereas crevice corrosion associated with SPC of the κIII phase occurs at biofouled and stressed areas of parent material. These factors, seldom simulated in physical tests, severely impact NAB’s corrosion resistance.
Keywords: Marine corrosion; Nickel aluminium bronze; Biofouling; Corrosion mechanisms; Residual stress; Plasma welding